Book Review - Jump, Alice (Columbia Journal of Environmental Law, 2020)
MOUNTAINS WITHOUT HANDRAILS: REFLECTIONS ON THE NA- TIONAL PARKS. By Joseph L. Sax. Ann Arbor, Mich.: The Uni- versity of Michigan Press, 1980. Pp. 152.